ANALISIS RASIO LIKUIDITAS DAN SOLVABILITAS PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA LEMATANG LAHAT (Jurnal Neraca: Jurnal Pendidikan dan Ilmu Ekonomi Akuntansi, 2019)
Abstract               The formulation of the problem in this research is how to analyze the liquidity ratio and solvency of Tirta Lematang Regional Water Company in Lahat Regency.               The purpose of this study was to determine the ratio of liquidity and solvency in the Tirta Lematang Regional Water Company in Lahat Regency. The object of the study of Tirta Lematang Regional Water Supply Company is Lahat Regency 2015-2017 period. The method used is qualitative descriptive.               The results of the liquidity ratio research of PDAM Tirta Lematang can be seen from the calculation of current ratio in 2015 (11.62%), 2016 (317.50%), and 2017 (0%). While the liquidity ratio is seen from the calculation with a quick ratio in 2015 (10.54%), 2016 (306.18%), and 2017 (0%). Based on the calculation of the liquidity and solvency ratios, it can be concluded that PDAM Tirta Lematang is in an unhealthy criteria because it is in accordance with the health assessment standards can be said to be healthy if> 65%. The solvency ratio of PDAM Tirta Lematang can be seen from the calculation of the debt to assets ratio in 2015 (345.54%), 2016 (17.00%) and 2017 (47.86%). The solvency ratio can be seen from the calculation of debt to equity ratio in 2015 (140.73%), 2016 (20.96%) and 2017 (91.80%). Based on the calculation of the liquidity and solvency ratios, it can be concluded that PDAM Tirta Lematang is in an unhealthy criteria because it is in accordance with the health assessment standards can be said to be healthy if> 65%.